HUBUNGAN GRIT DAN RESILIENSI PADA MAHASISWA PROGRAM STUDI BIMBINGAN DAN KONSELING UNIVERSITAS JAMBI - Marsyah Julianti; Muhammad Ferdiansyah; Muhammad Alridho Lubis (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2026)
This study is motivated by the importance of psychological readiness of students in the Guidance and Counseling Study Program at Universitas Jambi in facing various academic and non-academic demands. Problems commonly experienced by students include decreased motivation, feelings of hopelessness, and the risk of dropping out due to the inability to cope with academic pressures. Grit is a combination of perseverance and consistency of interest in achieving long-term goals. Meanwhile, resilience is the ability of individuals to bounce back from difficulties and adapt positively to pressure. This study is limited to two main variables, namely grit and resilience among active students of the Guidance and Counseling Study Program at Universitas Jambi. The indicators of grit include consistency of interest and perseverance of effort. The indicators of resilience include emotional regulation, impulse control, optimism, causal analysis, empathy, self-efficacy, and reaching out. The purpose of this study is to determine the level of grit, the level of resilience, and the relationship between grit and resilience among active students of the Guidance and Counseling Study Program at Universitas Jambi. This study uses a quantitative correlational research design. The sampling technique used is simple random sampling with a total sample of 211 respondents. The instrument used in this study is a Likert scale.The results show that the level of grit is in the high category with a percentage of 76%. The level of resilience is also in the high category with a percentage of 76%. The results of hypothesis testing using Spearman’s Rho correlation technique show a correlation coefficient value of r = 0.439 with a significance value of 0.000 < 0.05. This indicates a significant positive relationship between grit and resilience, which falls into the moderate correlation category